K42: an infrastructure for operating system research - Silva, Dilma Da; Krieger, Orran; Wisniewski, Robert W.; Waterland, Amos; Tam, David; Baumann, Andrew (Operating Systems Review, 2006)
K42 is an open-source scalable research operating system well suited to support systems research. The primary goals of K42's design that support such research include flexibility to allow a multitude of policies and implementations to be supported simultaneously, extensibility to allow new policies and implementations to be readily added, and scalability to enable good performance for both small and large applications on both small and large multiprocessor systems. The goals are accomplished via key features including an object oriented structure that allows specialized resource management implementations and policies on a per-resource, perapplication basis, implementation in user-level servers of much of the system functionality, and a sophisticated set of underlying services that provides a programming model for developing system software in a scalable and modular fashion. These characteristics make K42 an attractive framework for prototyping new operating system ideas. In addition, K42 has a sophisticated performance monitoring infrastructure allowing a thorough understanding of new ideas to be gained. The above framework combined with a consistent emphasis on scalability makes K42 well suited for high-end computing initiatives. In this paper, we describe the structure of K42 which contributes to the advantageous prototyping environment, and demonstrate how to utilize it by describing ongoing research eff orts.